Numerical analysis of soil bearing capacity by changing soil characteristics - Abdoullah Namdar; Mehdi Khodashenas Pelko (Fracture and Structural Integrity)
In this research work by changing different parameters of soil foundation like density, cohesion and foundation depth and width of square foundation at angle of friction of 0° to 50° with increment of 5°, numerically safe bearing capacity of soil foundation is calculated and it is attempted to assess economical dimension of foundation as well as understanding variation range of bearing capacity at different degree. It could help of civil engineering in design of foundations at any situation.